A High-Throughput QC-LDPC Decoder for Near-Earth Application - Li, Shixian; Zhang, Qichen; Chen, Yun; Zeng, Xiaoyang (International Conference on Digital Signal Processing proceedings, 2018)
Turbo-like decoding message passing (TDMP) scheduling, which is suitable for quasi-cyclic low-density parity-check (QC-LDPC) codes, can obtain better decoding performance and shorter convergence time than two-phase message passing (TPMP). Normalized min-sum algorithm (NMSA) is used to reduce complexity of soft message processing unit. In this paper, we propose a (8176, 7154) QC-LDPC decoder for Consultative Committee for Space Data Systems (CCSDS) standard. In order to avoid memory access conflicts, two cyclic-shifted identity matrices forming a submatrix are processed individually. The decoder is synthesized by TSMC 65nm CMOS process and can achieve a throughput of 4.1Gb/s at clock frequency of 380MHz.